Metodologi Pembelajaran Ilmu Nahwu dalam Pendidikan Bahasa Arab - A. Mualif (AL-HIKMAH (Jurnal Pendidikan dan Pendidikan Agama Islam), 2019)
Abstract This article deals with the method of teaching nahw in teaching Arabic. There are two common methods of teaching nahw in Arabic; they are method of alqiyasiyyah (method of sample) and method of alistiqrâiyyah (method of enduction). However, these two methods have their own advantages and disadvantages. Therefore, in teaching nahw, the teachers of Arabic should combine the two methods of teaching nahw based on the condition of the students the teachers will teach. Keywords: nahwu, learning Arabic language, learning method.